Role of thermal SiO2 on passivation of highly doped layer - Dastgheib-Shirazi, Amir; Hahn, Giso; Terheiden, Barbara (My University, 2019)
In this paper we investigate the influence of thermal oxidation during and after POCl3 diffusion. The main focus here is on the question of how far the presence of a thermally grown oxide layer has an influence on the emitter passivation. For this purpose, characterization methods such as electrochemical capacitance-voltage measurements and QSSPC are used. The novel finding of this paper is that in the case of a stack of passivation layers, the presence of the thermal oxide does not make a significant contribution to improved emitter passivation.
Keywords: 530